Cleaning up the paper trail – our clinical notes in open view. Issue 3 (16th April 2018) - Lambe, Gerard; Linnane, Niall; Callanan, Ian; Butler, Marcus W.
Abstract : Purpose: Ireland's physicians have a legal and an ethical duty to protect confidential patient information. Most healthcare records in Ireland remain paper based, so the purpose of this paper is to: assess the protection afforded to paper records; log highest risk records; note the variations that occurred during the working week; and observe the varying protection that occurred when staff, students and public members were present. Design/methodology/approach: A customised audit tool was created using Sphinx software. Data were collected for three months. All wards included in the study were visited once during four discrete time periods across the working week. The medical records trolley's location was noted and total unattended medical records, total unattended nursing records, total unattended patient lists and when nursing personnel, medical students, public and a ward secretary were visibly present were recorded. Findings: During 84 occasions when the authors visited wards, unattended medical records were identified on 33 per cent of occasions, 49 per cent were found during weekend visiting hours and just 4 per cent were found during morning rounds. The unattended medical records belonged to patients admitted to a medical specialty in 73 per cent of cases and a surgical specialty in 27 per cent. Medical records were found unattended in the nurses' station with much greater frequency when the ward secretary was off duty. Unattended nursing records were identified on 67 per cent of occasions the authors visited the ward and were most commonly found unattended in groups of six or more. Practical implications: This study is a timely reminder that confidential patient information is at risk from inappropriate disclosure in the hospital. There are few context-specific standards for data protection to guide healthcare professionals, particularly paper records. Nursing records are left unattended with twice the frequency of medical records and are found unattended in greater numbers than medical records. Protection is strongest when ward secretaries are on duty. Over-reliance on vigilant ward secretaries could represent a threat to confidential patient information. Originality/value: While other studies identified data protection as an issue, this study assesses how data security varies inside and outside conventional working hours. It provides a rationale and an impetus for specific changes across the whole working week. By identifying the on-duty ward secretary's favourable effect on medical record security, it highlights the need for alternative arrangements when the ward secretary is off duty. Data were collected prospectively in real time, giving a more accurate healthcare record security snapshot in each data collection point.